Best paper award in International Conference ACE 2012 - Tsapatsoulis, Nicolas (My University, 2026)
G. Tryfou, N. Tsapatsoulis Image indexing based on web page segmentation and clustering, Proceedings of the 11th International Conference on Applications of Computer Engineering (ACE '12), pp. 90-95, Athens, Greece, March 2012 (best paper award of ACE'12)
Keywords: Sciences